A Multidisciplinary Approach to Integrating Islamic Values and Local Culture into STEM Pedagogy in Arabic Language Learning - Sovia Fahraini; Muzakki Abdurrahman; Nada Ibrahim Alribdi; Muhammad Thohir; Moh Sholeh Afyuddin (Universitas Negeri Jakarta, 2026)
Arabic language learning has been dominated by traditional methods that emphasize memorization and analysis of classical texts, thus not supporting the development of 21st-century skills. This study aims to formulate an Arabic language learning model based on a multidisciplinary approach that integrates STEM, Islamic values, and local culture to create applicable, contextual, and meaningful learning experiences. The research method is a library research with a critical-analytical approach to the latest national and international literature, particularly those discussing STEM pedagogy, language learning, Islamic values-based education, and the local cultural context. The results of the study indicate that STEM integration allows Arabic to be used as a medium for exploration, discussion, and project production, while Islamic values ​​such as amanah (trust), adab, ta'āwun (respect), and ṣidq (compassion) serve as ethical guidelines in every activity. Local culture serves as a living and relevant context, strengthening motivation and meaning in learning. The proposed operational model emphasizes identification of real problems, linguistic exploration, cross-disciplinary integration, work production, and reflection and evaluation, in accordance with Vygotsky's principles of social constructivism. The contribution of this research is to present a holistic pedagogical framework that combines cognitive, affective, spiritual, and contextual aspects, so that Arabic language learning not only builds language competence, but also Islamic character, cultural awareness, and 21st-century skills that are relevant to global challenges.